Managing death in the ICU : the transition from cure to comfort - Curtis, J. Randall; Rubenfeld, Gordon D. (Oxford University Press, 2001)
This volume reviews the state of the art in caring for patients dying in the ICU, focusing on both clinical aspects of managing pain and other symptoms, as well as ethical and societal issues that affect the standards of care recieved, The book also addresses the changing epidemiology of death in this setting related to managed care, practical skills needed to provide the highest quality of care to terminal patients, communicating with patients and families, the mechanics of withdrawing life supporting therapies, and the essential role of palliative care specialists in the ICU. The book briefly describes unique issues that arise when caring for patients with some of the more common diseases that preciptate death in the ICU. Contributors for the book were chosed because they have experience caring for patients in the ICU, and are also doing current research to find ways to improve care for terminal patients in this setting.